2017
DOI: 10.1111/nph.14653
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific genetic diversity modulates plant–soil feedback and nutrient cycling

Abstract: Plant genetic diversity can affect ecosystem functioning by enhancing productivity, litter decomposition and resistance to natural enemies. However, the mechanisms underlying these effects remain poorly understood. We hypothesized that genetic diversity may influence ecosystem processes by eliciting functional plasticity among individuals encountering kin or genetically diverse neighbourhoods. We used soil conditioned by groups of closely related (siblings) and diverse genotypes of Deschampsia cespitosa - a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 61 publications
2
34
2
Order By: Relevance
“…As such, they are commonly assumed to be the cause of negative PSF driven by soil biota (e.g. Semchenko et al ., ; Kempel et al ., ). Root herbivores, such as root‐feeding nematodes, have received less attention, but can also cause negative PSF by feeding on the roots of young plants (Dias et al ., ).…”
Section: Primary Psf Mechanismsmentioning
confidence: 99%
“…As such, they are commonly assumed to be the cause of negative PSF driven by soil biota (e.g. Semchenko et al ., ; Kempel et al ., ). Root herbivores, such as root‐feeding nematodes, have received less attention, but can also cause negative PSF by feeding on the roots of young plants (Dias et al ., ).…”
Section: Primary Psf Mechanismsmentioning
confidence: 99%
“…In addition, growing on soil previously occupied by diverse plant genotypes increased nitrogen uptake in roots of D . cespitosa compared with soil conditioned by siblings (Semchenko et al ., ) and a role of soil microbiome was suggested.…”
Section: Neighbour Detection and Response Strategiesmentioning
confidence: 99%
“…Depending on the source of phosphate available in the soil, the grass Deschampsia cespitosa produces more biomass when grown with a different grass species than with conspecifics, suggesting that nutrient availability regulates plant competition (Ahmad-Ramli et al, 2013). In addition, growing on soil previously occupied by diverse plant genotypes increased nitrogen uptake in roots of D. cespitosa compared with soil conditioned by siblings (Semchenko et al, 2017) and a role of soil microbiome was suggested.…”
Section: Nutrients Uptake and Foragingmentioning
confidence: 99%
“…The plants also had limited access to mineralised nutrients due to litter being confined to a litterbag that excluded plant roots, even though mineralised nutrients could diffuse from the litterbag into the soil solution. Future studies should consider using litter mixed directly into the soil when estimating the effects of litter decomposition on plant-soil feedback (Semchenko et al 2017). …”
Section: Discussionmentioning
confidence: 99%